EVALUASI KELAYAKAN PEMBIAYAAN MURABAHAH PADA PT BPRS KARYA MUGI SENTOSA KANTOR CABANG MOJOKERTO - Fandawati, Ranieta Ratnasari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The evaluation of murabahah financing is an important element in giving the financing to the customers. The activities of granting this financing requires a good and thorough analysis to all funding aspect that can support the process of giving the funding, in order to prevent from the funding given. The purpose of this research is to find out the feasibility of granting financing provided by PT BPRS Karya Mugi Sentosa Branch Office Mojokerto. Type of this research is qualitative research with descriptive approach. The data collection technique is using survey method through documentation and interview. Tha data source is using primary data and secondary data which are taken from 4 customers. From that the data obtained later made an analysis financing by using 5c analysis technique, namely character, capacity, capital, collateral, and condition and as tool feasibility judgment. Based on the financing analysis which has been done, it obtains that the four subjects clients deserve the funding provided by PT BPRS Karya Mugi Sentosa Branch Office Mojokerto. It can be seen from the analysis result of 5C, all of four customers have a good character, and have the ability to pay back the fund being proposed, have sufficient capital, have the collateral which can cover the proposed fund and good condition of business. Keywords : Murabahah Financing, 5C Analysis, Financing Analysis